A methodology for wellbore stability analysis in anisotropic formations: A case study from the Canning Basin, Western Australia - Gholami, Raoof; Aadnoy, B.; Foon, L.; Elochukwu, H. (Elsevier Inc., 2017)
© 2016 Elsevier B.V.Stability analysis of directional wells has been a long standing issue due to complexity of geological settings and changes in the stress coordinate system when wells are being deviated. Although there have been many studies developing strategies to estimate the safe mud weight based on wellbore geometry and anisotropy of subsurface structures, the issue of instability in deviated wellbores has been widely experienced in many fields around the world, especially in Malaysia and Australia. The aim of this paper is to present a workflow for estimation of geomechanical parameters and stress states of boreholes drilled directionally into anisotropic formations. A case study from one of the wells drilled into tight shales was brought into attention to evaluate the application of the proposed methodology. The results obtained based on the interpretations of data and reports of similar incidents in the field indicated that the well was deviated due to drilling parallel to the direction of bedding planes, causing creation of blocky, and tabular cuttings with parallel surfaces at shakers. The Horizontal Transverse Isotropic (HTI) model was assumed and the ANNIE model, developed exclusively for shales, was considered for estimation of stiffness parameters required to fully characterize shale formations. Determination of the safe mud weight window using two well-known failure criteria with proven applications revealed that a three-dimensional failure criterion should have been applied to prevent the instability of the wellbore wall. In fact, following the underestimation of shear failure provided by the Mohr-Coulomb criterion, a 13 ppg mud would have been selected to save the well, which in turn could result in enlargements of the well and significant increase of completion costs. Although some practical conclusions are provided, more studies are required to evaluate the application of the proposed methodology in other wells worldwide.